Identification, production and bioactivity of casein phosphopeptides – A review. (July 2022) - Tenenbaum, Mathie; Deracinois, Barbara; Dugardin, Camille; Matéos, Aurélie; Romelard, Audrey; Auger, Julie; Boulier, Audrey; Ravallec, Rozenn; Flahaut, Christophe; Cudennec, Benoit
Graphical abstract: Highlights: CPPs are bioactive phosphorylated peptides resulting from the hydrolysis of caseins. Recent analytical techniques permit better characterization of CPPs. Gastrointestinal digestion impacts CPP biological activities. CPPs are chelating peptides improving essential mineral bioavailability. CPP preparations are promising for functional foods development. Abstract: Milk and dairy products are significant sources of proteins and peptides impacting human health. In this way, the interest in CPPs, bioactive phosphorylated peptides resulting from the hydrolysis of caseins, has grown in the past years. CPPs were mainly studied for their capacity to chelate and increase the bioavailability of essential minerals involved in multiple physiological processes. Moreover, CPPs harbour interesting antioxidant and anti-inflammatory properties. Recent in vivo and in vitro studies demonstrated that these different roles are strongly linked to the intrinsic properties of CPPs and CPP concentrate preparations. This review first comments on the different methods of CPP analytical characterization, focusing on recent techniques. Then, the CPP release occurring during the gastrointestinal digestion was reviewed, followed by the different CPP obtention processes and their impact on their physicochemical characteristics. Finally, the different bioactive roles attributed to CPPs, including mineral chelating properties, are discussed. We show that CPPs have a promising role in treating various pathologies, notably to compensate for deficiencies in certain nutrients and an anti-oxidant and anti-inflammatory role. Nevertheless, the mechanisms by which CPPs exert their role remain to be elucidated, and this requires precise characterization of CPPs. This work highlights the key parameters to be considered to study and produce CPPs and the different ways to be investigated in the future to elucidate their roles in vivo and characterize their potential for human health.